1992
DOI: 10.1111/j.1365-2125.1992.tb04120.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bronchial effects following topical administration of butylamino‐phenoxy‐propanol‐acetate, an oculoselective beta‐ adrenoceptor blocker in asthmatic subjects.

Abstract: 1 Butylamino-phenoxy-propanol-acetate (BPPA) is a new topical oculoselective Padrenoceptor blocker for the reduction of intraocular pressure (IOP) in man. Its potency on the airways of normal subjects was identical with that of placebo. A study was carried out to determine the potential of BPPA to cause bronchoconstriction in mild asthmatics (FEV1 . -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Nevertheless, in contrast to timolol, there was no evidence of systemic b-adrenoceptor blockade [134]. In addition, cumulative concentrations of L-653,328 up to 4% did not cause bronchoconstriction in asthmatic patients [135]. Despite these, L-653,328 cannot be considered a true soft drug because its hydrolytic cleavage releases an active alcohol, L-652,698.…”
Section: Inactive Metabolite-based Soft Drugsmentioning
confidence: 95%
“…Nevertheless, in contrast to timolol, there was no evidence of systemic b-adrenoceptor blockade [134]. In addition, cumulative concentrations of L-653,328 up to 4% did not cause bronchoconstriction in asthmatic patients [135]. Despite these, L-653,328 cannot be considered a true soft drug because its hydrolytic cleavage releases an active alcohol, L-652,698.…”
Section: Inactive Metabolite-based Soft Drugsmentioning
confidence: 95%
“…However, in contrast to timolol, there was no evidence of systemic β-adrenoceptor blockade . In a follow-up study, it was observed that cumulative concentrations of L-653,328 up to 4% did not cause bronchoconstriction in asthmatic patients …”
Section: β-Adrenoceptor Antagonistsmentioning
confidence: 96%
“…Relativamente a este tema foram incluídos três estudos referentes ao uso de beta-bloqueantes oculares tópicos em doentes asmáticos: um coorte 9 e dois ensaios clínicos randomizados duplo-cegos. 16,21 O coorte com 693 doentes, que avaliou os agentes timolol (não seletivo) e betaxolol (cardioseletivo) em doentes com asma e DPOC estudados num grupo conjunto, concluiu que, em relação a outros fármacos não beta-bloqueantes no tratamento crónico tópico antiglaucoma, tanto o timolol como o betaxolol aumentaram os dias de internamento hospitalar (em 20,7 dias e 23,1 dias, respetivamente, por 100 anos de tratamento antiglaucoma) e a frequência de idas ao serviço de urgência (em 6,1 e 7,3 idas, respetivamente, por 100 anos de terapêutica). 9 Um dos ensaios clínicos randomizado estudou a administração de altas concentrações de BPPA (butilamino-fenoxi-propanol-acetato -um beta-bloqueante tópico oculoseletivo usado para reduzir a pressão intraocular), timolol e placebo em 12 doentes asmáticos com pressão intraocular normal.…”
Section: Atenolol -11unclassified
“…Ocorreram reduções dose dependentes no FEV1 (média de 23,33%) e no sGaw (média de 55,41%), bem como sintomas respiratórios adversos em todos os doentes (taquipneia, dispneia e/ou tosse) com o uso de timolol, mas não ocorreram tais alterações com o BPPA, sugerindo-se, assim, que este agente poderá ter maior margem de segurança em relação ao timolol. 16 O outro ensaio clínico randomizado envolveu 10 doentes que tinham broncoconstrição com gotas oculares de timolol e testou a exposição a gotas oculares de L-414,465 (R-enantiómero do timolol), o qual também mostrou reduzir de forma dose dependente o sGaw e FEV1, embora quatro vezes menos que o timolol. 21 Apesar desta diferença, os autores concluem que o L-414,465 não tem maior margem de segurança que o timolol e não tem, portanto, maior vantagem no seu uso clínico.…”
Section: Atenolol -11unclassified